Estrategias tácticas para mejorar las dinámicas comerciales de la industria farmacéutica en Colombia (2022)
The objective of this research was to formulate tactical strategies to improve the commercial dynamics of the pharmaceutical industry in Colombia. For this, a descriptive qualitative study was carried out using the documentary review and the Regional Map of Opportunities (MARO) of the Productive Colombia program of the Ministry of Commerce, Industry and Tourism. It was concluded that the pharmaceutical industry is complex and competitive that requires a constant process of research and development (R&D) and therefore, investment to develop and produce new drugs or manufacture existing ones whose economic structure is constituted by the triad: consumer, entities providing health services and entities in charge of mitigating the expenses and costs that are generated in the care of said services. On the other hand, given the diversity of markets that are part of the industry, governments should tend to strengthen the commercial dynamics (imports and exports) seeking to meet the needs of the population but also obtaining profits and income as part of the socioeconomic development for which should tend, that in the case of Colombia, in the last five years (2017 - 2021) there have been more imports (42.9%) than exports (9.2%) that have been made, establishing a wide difference of 33.7%. For this reason, a series of tactical strategies were formulated aimed at strengthening and improving said panorama in terms of exports, taking advantage of the potential that the country has in the different subsectors that comprise it.